Controlling the operating conditions in an Operating Room - Rosa, C. (2014)
In this paper, we describe the development of a module capable of controlling environmental conditions, personnel movement and management of other important parameters for an operating room (OR) or surgery block. The base of assembly uses a real-life small scale model trying to simulate the systematic functionality of an OR as well as its crucial components. These include the regulation of environmental parameters, logging of entries and exits by the staff, management of pharmaceutical drugs and diseases, and the statistical analysis of several acquired data. The project integrates different types of technologies, such as the microcontroller Arduino, a bidirectional communication interface between this device and a computer, a web based user interface for dynamic interaction, as well as database concepts for data management.